Abortive Phage Resistance Mechanism AbiZ Speeds the Lysis Clock To Cause Premature Lysis of Phage-Infected Lactococcus lactis - Durmaz, Evelyn (American Society for Microbiology, 2007)
The conjugative plasmid pTR2030 has been used extensively to confer phage resistance in commercial Lactococcus starter cultures. The plasmid harbors a 16-kb region, flanked by insertion sequence (IS) elements, that encodes the restriction/modification system LlaI and carries an abortive infection gene, abiA. The AbiA system inhibits both prolate and small isometric phages by interfering with the early stages of phage DNA replication. However, abiA alone does not account for the full abortive activity reported for pTR2030. In this study, a 7.5-kb region positioned within the IS elements and downstream of abiA was sequenced to reveal seven additional open reading frames (ORFs). A single ORF, designated abiZ, was found to be responsible for a significant reduction in plaque size and an efficiency of plaquing (EOP) of 10(−6), without affecting phage adsorption. AbiZ causes phage φ31-infected Lactococcus lactis NCK203 to lyse 15 min early, reducing the burst size of φ31 100-fold. Thirteen of 14 phages of the P335 group were sensitive to AbiZ, through reduction in either plaque size, EOP, or both. The predicted AbiZ protein contains two predicted transmembrane helices but shows no significant DNA homologies. When the phage φ31 lysin and holin genes were cloned into the nisin-inducible shuttle vector pMSP3545, nisin induction of holin and lysin caused partial lysis of NCK203. In the presence of AbiZ, lysis occurred 30 min earlier. In holin-induced cells, membrane permeability as measured using propidium iodide was greater in the presence of AbiZ. These results suggest that AbiZ may interact cooperatively with holin to cause premature lysis.